Microglia: A Potential Therapeutic Target for Sepsis-Associated Encephalopathy and Sepsis-Associated Chronic Pain - Li, Yi; Yin, Lu; Fan, Zhongmin; Su, Binxiao; Chen, Yu; Ma, Yan; Zhong, Ya; Hou, Wugang; Fang, Zongping; Zhang, Xijing (Frontiers in Pharmacology, 2020)
Neurological dysfunction, one of the severe manifestations of sepsis in patients, is closely related to increased mortality and long-term complications in intensive care units, including sepsis-associated encephalopathy (SAE) and chronic pain. The underlying mechanisms of these sepsis-induced neurological dysfunctions are elusive. However, it has been well established that microglia, the dominant resident immune cell in the central nervous system, play essential roles in the initiation and development of SAE and chronic pain. Microglia can be activated by inflammatory mediators, adjacent cells and neurotransmitters in the acute phase of sepsis and then induce neuronal dysfunction in the brain. With the spotlight focused on the relationship between microglia and sepsis, a deeper understanding of microglia in SAE and chronic pain can be achieved. More importantly, clarifying the mechanisms of sepsis-associated signalling pathways in microglia would shed new light on treatment strategies for SAE and chronic pain.